Robert's uterus (asymmetric septate uterus): a rare congenital Müllerian duct anomaly. Issue 5 (6th May 2022) - Dunphy, Louise; Taylor, Sian; Whitby, Elspeth H; Agarwal, Umber; Alfirević, Žarko
Abstract : Müllerian anomalies such as Robert's uterus, which was first described by the French gynaecologist Dr Helene Robert in 1969, are rare clinical entities and have been reported in <3% of the female population. Robert's uterus is a rare phenomenon with a relative dearth of reported cases. Affected individuals may present with pelvic pain and dysmenorrhoea that intensifies near menses or acutely, with severe abdominal pain to the emergency department. They are also associated with adverse pregnancy outcomes, abnormal fetal presentation, preterm labour, recurrent pregnancy loss and infertility. Although ultrasound has a role in its initial assessment, MRI is the best modality to further delineate its anatomy. It is typically managed via laparotomy and total horn resection, endometrectomy of the blind cavity or abdominal metroplasty. The authors present the case of a 40-year-old woman at 19+3 weeks gestation with acute onset of left-sided abdominal pain. A transvaginal ultrasound and MRI of the pelvis confirmed a Robert's uterus with a viable pregnancy in the upper left horn. She developed a ruptured horn with significant haemoperitoneum. An emergency laparotomy was performed and a non-viable fetus was evident. Only a few cases of pregnancy in the blind hemicavity have been reported so far. This case also highlights the importance of considering this diagnosis in young females presenting with dysmenorrhoea and normal menstrual flow. It is imperative to render a prompt diagnosis, as minimally invasive procedures may be more effective if detected before the formation of adnexal endometriomas.